2014
DOI: 10.1111/exd.12552
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia yeasts activate the NLRP3 inflammasome in antigen‐presenting cells via Syk‐kinase signalling

Abstract: Although being a normal part of the skin flora, yeasts of the genus Malassezia are associated with several common dermatologic conditions including pityriasis versicolour, seborrhoeic dermatitis (SD), folliculitis, atopic eczema/dermatitis (AE/AD) and dandruff. While Malassezia spp. are aetiological agents of pityriasis versicolour, a causal role of Malassezia spp. in AE/AD and SD remains to be established. Previous reports have shown that fungi such as Candida albicans and Aspergillus fumigatus are able to ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 60 publications
3
77
1
Order By: Relevance
“…and C . albicans recognized by C-type lectin receptors transduce signals to induce NLRP3 inflammasome activation in macrophages and DCs [19, 20, 23]. M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and C . albicans recognized by C-type lectin receptors transduce signals to induce NLRP3 inflammasome activation in macrophages and DCs [19, 20, 23]. M .…”
Section: Discussionmentioning
confidence: 99%
“…Malassezia spp. triggers IL-1β production in human monocyte-derived DCs through Dectin-1 [19]. TLR-2 and Dectin-1 are both involved in induction of pro-IL-1β transcription by hyphal forms of C .…”
Section: Discussionmentioning
confidence: 99%
“…These include PAMPs such as LPS, fungal zymosan, bacterial toxins, and also the bacteria Listeria monocytogenes (Meixenberger et al, 2010), S. aureus (Munoz-Planillo et al, 2009), and Propionibacterium acnes (Kistowska et al, 2014b; Qin et al, 2014), as well as yeasts like Candida albicans (Hise et al, 2009) and of the Malassezia spp. (Kistowska et al, 2014a). NLRP3 can also be activated by danger-associated molecules that are not derived from pathogens but often associated with cellular stress, the so-called DAMPs, including extracellular ATP (Mariathasan et al, 2006), asbestos (Dostert et al, 2008), amyloid-β (Halle et al, 2008), DNA:RNA hybrids (Kailasan Vanaja et al, 2014), and crystals such as gout-causing monosodium urate (MSU) (Martinon et al, 2006), silica (Dostert et al, 2008), or cholesterol (Duewell et al, 2010).…”
Section: The Inflammasomesmentioning
confidence: 99%
“…The etiological agent of pityriasis versicolor, Malassezia was shown to activate the NLRP3 inflammasome via the dectin-1 and Syk signaling cascade, causing the release of IL-1β (Kistowska et al, 2014a). To date, no IL-1 blocker has been evaluated for the treatment of Malassezia- associated skin diseases.…”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 99%
“…Kistowska et al showed that different species of Malassezia present the potential to activate the NLRP3 inflammasome in antigen-presenting cells, leading to a high synthesis of IL-1β. 107 …”
Section: Dermatological Diseases Associated With Inflammasomesmentioning
confidence: 99%